Molecular dynamics simulations of loading and unloading of drug molecule bortezomib on graphene nanosheets. Issue 15 (28th February 2020) - Zeng, Songwei; Ji, Yu; Shen, Yue; Zhu, Ruiyao; Wang, Xiaogang; Chen, Liang; Chen, Junlang
Abstract : Graphene-drug complexes can enter the lipid bilayer and then drug molecules release from graphene surface. Abstract : Graphene has been regarded as one of the most hopeful candidates for transporting drugs to target cells because of its huge surface area and high cellular uptake. In this work, we performed molecular dynamics simulations to investigate the potential application of graphene as a substrate to carry and deliver drug molecules. Bortezomib (BOR) was selected as a model drug, as its atomic structure and polarity are suitable to be adsorbed on pristine graphene (PG) and graphene oxide (GO). First, BOR molecules are loaded on graphene surface to form graphene–BOR complexes, then these complexes readily enter the lipid bilayer and finally BOR releases from graphene surface into the membrane. The entry of graphene–BOR complexes into the membrane is mainly driven by the hydrophobic interactions between lipid tails and the basal plane of nanosheets, while the electrostatic interaction between the polar groups of BOR and lipid headgroups contributes to the release of BOR from graphene into the membrane. Different from PG, BOR molecules are hard to remove from GO surface after the complex enters the lipid bilayer. The electrostatic attraction from the oxygen-containing groups enhances the binding of BOR on GO. Potential of mean force calculations confirm that BOR on GO has lower free energy than it adsorbed on PG surface. The results indicate that the adsorption intensity and release rate of graphene nanosheets can be tuned by oxidation and electrification, and graphene served as substrate to transport and release particular drug molecules is feasible.